Applications of Artificial Intelligence in Higher Education in Algeria - BETATACHE, Radia (Journal of Ecohumanism, 2026)
This research paper aims to explore the applications of artificial intelligence in higher education in Algeria, in light of the growing interest among university lecturers, researchers, and students in using its applications in the field of higher education. The Algerian State has also attached great importance to this area. The study concluded that the application of artificial intelligence in higher education has become an unavoidable necessity, given the advantages it offers. It also emphasises the need to provide an appropriate environment for its proper and safe use, and training in its use.